DYNAMICS OF PATHOLOGICAL PROCESSES IN FORESTS OF KHARKIV REGION FOR THE PERIOD OF 1992–2012 - Ustskiy, I. M.; Mykhailichenko, O. A. (Forestry and Forest Melioration, 2018)
Introduction To understand the causes of the presence and development of pathological processes, first of all, it is necessary to follow their dynamics in different regions of Ukraine. This will enable researchers to predict certain pathological processes emergence and, accordingly, to prevent their development. The known and predicted process that influences development of all biological objects on earth is the dynamics of solar activity, which is characterized by the Wolf number. The results of the forecast based on the generalization of the data on forest decline in Ukraine from 1992 through 2009 indicated that by year 2020, the pathological processes will have been observed on 12,2% of the forested areas. At that, if the current tendency remains in Ukraine, in 2020, pine forests with forest-pathological processes will cover 140 thousand ha, oak forests – 230 thousand ha and fir forests – about 500 thousand ha. The aim of the research was to investigate special aspects of the forest-pathological processes in forests in Kharkiv Region, which took place from 1992 through 2012 as the most characteristic for the conditions of the Left-Bank Forest-Steppe of Ukraine. Materials and Methods To study the dynamics of the scale of the forest-pathological processes, we collected all available information for the period from 1992 through 2009 concerning that in stands with different species, the causative reasons and extent of their distribution. Then we generalized obtained information. Dieback is considered pathological if trees of the 1st and 2nd Kraft classes die. Since 1994 the data in such stands have been collected and generalized every third year by means of the developed methodology. To evaluate the extent of the pathological processes distribution, we calculated a part of the area of one or another dying species with respect to the total area covered with that species. Based on that figure, we worked out a gradation for the pathological processes extent: 0.1–2.4% – weak; 2.5–5.0% – average; 5.1–10.0% – strong; 11.0–15.0% – very strong; 15.1–20.0% – critical; > 20.0% – ecological catastrophe of the district-, region- or territory scale. The reasons for forest stand decline or deterioration of health condition were mostly determined hypothetically, apart from obvious cases such as fires, windfalls and icing. We considered predictibility of the forest-pathological processes scale based on the correlation of the plot area with pathological processes and averaged Wolf numbers during the monitoring period. Results From 1992 (as of 1994) the pathological processes scale had gradually and unevenly increased by 2009. Furthermore, it significantly decreased by 2012 (8.7 thousand ha less). The highest level of pathological processes for the last 20 years was noted in oak stands and somewhat lower one in pine forests, which is 59,5% and 36,9% of the total area with the pathological processes. Over the past 20 years the area of dying stands with other species has made 3.6%. At that, the largest area was occupied by aspen stands (1.3%), somewhat smaller areas by red oak stands (0.8%), ash stands (0.4%), Crimean pine (0.3%), poplar (0.2%) and alder ones (0.1%). A high rate of the pathological processes distribution was observed in 1997, 2003, 2006, and 2012. As of 2009, the spread of pathological processes had reached a very high level. From 1994 through 2009 pathological processes gradually increased in oak stands Diseases remain the constant and significant factor in stand decline. For 20 years of observation, the proportion of stands where the condition got worsened due to diseases, was gradually and unevenly increasing. As of 2006, 2009, and 2012, it reached 27.0%, 50.0% and 59.0%, respectively. The impact of pests on the health of the stands was detected as of 1994, 1997, 2000, and 2003, and most significantly as of 1997 (36.0%). Furthermore, we did not detect any impact of pests on the condition of the stands as of 2006, 2009, and 2012. Moreover, during all periods of the research, the exact causes of stand health deterioration have not been proven in from 5.0 to 43.0% of the cases. The main factors of deterioration of the pine stands condition from 1992 through 2012 were diseases (mainly root rot by Heterobasidion annosum Fr. (Bref)). They were noted on 69.0 % of the areas whose condition deteriorated for various reasons. A fire as a deterioration factor for pine forests was detected for 7.0 % of all the plots where dieback occurred. We observed other factors as a cause of dieback on small areas. They were climatic and hydrological phenomena and made 2.7 and 2.5 % of all the factors, respectively. We found out that the scale of forest-pathological processes is in the inverse and correlated dependence on solar activity. The correlation analysis between the Wolf numbers for that period and the scale of pathological processes showed a moderate inverse relationship between them. However, the magnitude of the relationship between solar activity and the area of dying oak stands was less strong than that of the dying pine forests – r0.01 = -0.473 and r0.01 = -0.781, respectively. Dynamics of solar activity for 2012–2020 showed that its peak in 2014 was the lowest since 1928. Moreover, in subsequent years up to 2018–2020, taking into account forecasts, the activity of the sun will also be low, that is, the area of dying forest stands will increase. Conclusions In Kharkiv forests the largest scale of pathological processes during1992–2012 was characteristic to oak stands and pine stands – 59.5% and 36.9% of the total area where pathological processes were discovered. A high degree of pathological processes in forest stands of Kharkiv Region was observed in 1997, 2003, 2006, and 2012. As of 2009, the spread of pathological processes became very strong (13.3% of the total forested area). The prevailing reasons for the deterioration of the oak health over the entire period of research were diseases – 32.0%, water regime changes – 15.0%, climatic factors – 11.0%, and insect damage – 7.0%. As for the pine stands, the major factors for the deterioration of their condition were diseases, mainly root rot – 69.0% and fires – 7.0 %. Some other factors were observed on small areas. We found out that the magnitude of the relation between solar activity and the area of dying oak stands was less strong than that of the dying pine forests. Thus, by 2020 the area of forests with pathological processes will have increased. 1 Fig., 4 Tables, 8 Refs.